TINGKAT KEPUASAN PETERNAK AYAM BROILER TERHADAP POLA KEMITRAAN MODEL CONTRACT FARMING DI KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR (Studi Kasus : PT. Gemilang Unggas Prima) - Catur Subiyanto; Cepriadi '; Eri Sayamar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research to analyze partnership implementation which has ran by PT. Gemilang Unggas Prima. Analyze the level of satisfaction plasma farmer on the implementation of partnership PT. Gemilang Unggas Prima. Research sites in the District of Kampar Kiri Tengah, Kampar Regensy. Interpretation sample method is usedpurposive sampling method which partnership minimal 3 periods who made respondents. There are 18 farmers who partnered on the PT. Gemilang Unggas Prima. Type of research is descriptive using quantitative and qualitative data. To collect data was done through interviews by questionnaires. Data analysis is descriptive used(Customer Satisfaction Index) CSI and (importance performance analysis) IPA. Result shows of the analysis partnership was indicated partnership pattern run of PT. Gemilang Unggas Prima is the plasma core system with the modelcontact farming bi-part, between companies and farmers are concerned with the letter of cooperation agreement, which in there are provisions of the right and obligation that must be meet by the companies and farmers. Other than, that the contract price of feed, DOC, and live chickens agreed in contract price determined by company. Result shows of the analysis satisfaction index of farmers(Customer Satisfaction Index) obtained 81, 20 % it means farmers are very satisfied with the performing of PT. Gemilang UnggasPrima. Based on the analysis (importance performance analysis) are variable that should be improved in performance company is the quality of variable fowl tools production.   Keywords :Satisfaction level, partnership, contract farming, broiler.